The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/2049463714549776
|View full text |Cite
|
Sign up to set email alerts
|

‘It makes you think’ – exploring the impact of qualitative films on pain clinicians

Abstract: Background: Researchers need to consider the impact and utility of their findings. Film is an accessible medium for qualitative research findings and can facilitate learning through emotional engagement. Aim: We aimed to explore the usefulness of a short film presenting findings from a published qualitative synthesis of adults' experience of chronic musculoskeletal pain for pain education. In particular, we were interested in the impact of the film on clinician's understanding of patients' experience of chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…Furthermore, previous research found presentation of qualitative findings of pain research through film had useful learning potential for clinicians. 42 Qualitative research has the potential to incorporate the patient voice into the design of healthcare services. 43 The study was undertaken in the context of an increasing emphasis on self-management of long-term conditions from the Scottish Government.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Furthermore, previous research found presentation of qualitative findings of pain research through film had useful learning potential for clinicians. 42 Qualitative research has the potential to incorporate the patient voice into the design of healthcare services. 43 The study was undertaken in the context of an increasing emphasis on self-management of long-term conditions from the Scottish Government.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Each year over five million people in the UK develop chronic non-malignant pain [ 7 ], and healthcare professionals (HCPs) can find it a challenge to effectively treat this pain. For example, they can find it difficult if they are unable to offer the patient a solution [ 8 ], or if they have to refuse patients’ requests for a particular test or treatment [ 9 , 10 ]. Despite recent USA [ 11 ] and UK guidelines [ 12 ] suggesting that patients with chronic non-malignant pain might not gain benefits, opioids are commonly prescribed for uncontrolled persistent pain, and there has been a significant rise in opioid prescription [ 13 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data were then entered into NVivo 8 qualitative analysis software package. Results are organised around themes that emerged from the transcripts [ 35 ]. Quotes presented in Table 2 and discussed in the following section represent examples of the identified themes with narrative accounts provided to show the participants’ shared experience [ 36 ].…”
Section: Methodsmentioning
confidence: 99%